إدارة التميز ودورها في تحسين أداء العاملين في المؤسسة الجزائرية - خلوط, محمد; شوية, صلاح الدين (University of Eloued جامعة الوادي, 2023)
ملخص الدراسة بالعربية هدفت دراستنا للتعرف على إدارة التميز ودورها في تحسين أداء العاملين في المؤسسة الجزائرية- دراسة حالة مؤسسة اتصالات الجزائر بالوادي-وقد انطلقنا منالإشكالية التالية: هل تساهم إدارة التميز في تحسين أداء العاملين بوحدة اتصالات الجزائر بالوادي؟ وقد أدرجنا تحته الأسئلة الفرعية التالية: - هل تحقق إدارة التميز تحسين في التسيير الإداري للمؤسسة الجزائرية بوحدة اتصالات الجزائر بالوادي؟ - هل تحقق إدارة التميز تحسين في الخدمة العمومية للمؤسسة الجزائرية بوحدة اتصالات الجزائر بالوادي؟ - هل تحقق إدارة التميز تحسين في السلوك التنظيمي للمؤسسة الجزائرية بوحدة اتصالات الجزائر بالوادي؟ وقد اعتمدنا في هذه الدراسة على المنهج الوصفي التحليلي، وتم الاعتماد على العينة العشوائية البسيطة نظرا لطبيعة الموضوع المدروس، كما تم استخدام أداة الاستبيان لجمع المعطيات،وقد خلصنا في دراستنامن تحقق الفرضيات الثلاث كما يلي: - أن إدارة التميز حققت تحسين في التسيير الإداري للمؤسسة الجزائرية بوحدة اتصالات الجزائر بالوادي. - كما حققت تحسينفي الخدمة العمومية للمؤسسة الجزائرية بوحدة اتصالات الجزائر بالوادي. - وأيضا حققت تحسين في السلوك التنظيمي للمؤسسة الجزائرية بوحدة اتصالات الجزائر بالوادي. Study Summary in English: Our study aimed to identify digital management and its role in improving public service - a case study of the Biometric Authority of the Valley Municipality, and we started from the following problem: Does the Excellence Department contribute to improving the performance of the employees of the Algeria Telecom Unit in El-Oued? Under it we have included the following sub-questions: - Does the Department of Excellence achieve improvement in the administrative management of the Algerian institution in the Algeria Telecom Unit in El Oued? - Does the Department of Excellence achieve improvement in the public service of the Algerian institution in the Algeria Telecom Unit in El Oued? - Does the Excellence Department achieve improvement in the organizational behavior of the Algerian institution in the Algeria Telecom Unit in El Oued? In this study, we relied on the analytical descriptive approach, and the simple random sample was relied on due to the nature of the subject studied, and the questionnaire tool was used to collect data, and we concluded in our study that the three hypotheses were verified as follows: - The Department of Excellence has achieved an improvement in the administrative management of the Algerian institution in the Algeria Telecom Unit in El Oued. - It also achieved an improvement in the public service of the Algerian institution in the Algeria Telecom Unit in El Oued. - It also achieved an improvement in the organizational behavior of the Algerian institution in the Algeria Telecom Unit in El Oued.
دراسة ميدانية على عينة بمؤسسة اتصالات الجزائر ـ الوادي
مذكرة ماستر في علم الاجتماع تخصص تنظيم وعمل
Keywords: إدارة التميز، gestion de l'excellence, gestion de l'excellence; أداء العاملين، performances des employés, employee performance